Luminescence Properties of Eu- and Mg-Codoped Sol-Gel SiO2 Glasses. (5th June 2012) - Onani, Martin O.; Mushonga, Paul; Koao, Lehlohonolo F.; Dejene, Francis B.
Abstract : A series of SiO2 nanostructures codoped with Eu 3+ ; Mg 2+ ions were obtained by a sol-gel method. The gels synthesized by the hydrolysis of Si(OC2 H5 )4, Eu(NO3 )3 ·6H2 O, and Mg(NO3 )2 were heated in air at 600 ° C for 2 hours. Firstly, the total amount of Eu 3+ ions was varied from 0 to 2.0 mol% to investigate the effect of self-damping, while in the second case, the Eu 3+ ions were kept constant in the experiment at 0.5 mol% total doping and Mg 2+ ions varied. The samples were characterized by X-ray diffraction, TEM, EDS, and UV lamp-excited luminescence spectroscopy. The Eu 3+ ions were homogeneously dispersed in the silica and interacting with the small (1–5 nm) amorphous silica matrix. Strong red emissions located at 614 nm and 590 nm for doped and codoped SiO2 were observed from the UV light excitation at room temperature. The composition of around 1.25 mol% Eu 3+ gave highest emission intensity. SiO2 ; Mg 2+ ions portray strongly enhanced emissions due to energy transfer from Mg 2+ to Eu 3+, which is due to radiative recombination. An increase in luminescence intensity was observed as the Mg 2+ -to-Eu 3+ ratio increased for the range investigated. The results show Eu 3+ ion is located inside or at the surface of disordered SiO2 nanoparticles.